2000
DOI: 10.3354/meps208001
|View full text |Cite
|
Sign up to set email alerts
|

Microzooplankton grazing activity in the temperate and sub-tropical NE Atlantic: summer 1996

Abstract: ) and oligotrich ciliates (0.7 µg C l -1 ) were more important at the southerly station. Tintinnids and 'other' ciliates contributed less to the total microzooplankton abundance or biomass. We conclude that microzooplankton formed a significant component of the food web in the NE Atlantic and were important controllers of phytoplankton production, particularly in temperate waters, during this investigation period. Our data suggest that microzooplankton grazing did not control the picoplankton production in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 43 publications
3
31
1
Order By: Relevance
“…The significant grazing pressure that we observed is consistent with the results of previous work within the JGOFS and BOFS studies of prymnesiophytedominated phytoplankton communities in the North Atlantic spring bloom (Burkill et al 1993, Verity et al 1993b, Fileman & Leakey 2005. These studies and others include reports of microzooplankton dominance of total phytoplankton herbivory and microzooplankton consuming significant portions of phytoplankton daily production in the North Atlantic (Gifford et al 1995, Stelfox-Widdicombe et al 2000.Increases in microzooplankton abundance and grazing mortality by Day 8 of the experiment in the 2 high temperature treatments were consistent with the known effects of increased temperature on protistan Mar Ecol Prog Ser 388: [27][28][29][30][31][32][33][34][35][36][37][38][39][40] 2009 physiological rate processes (Eppley 1972, Rose & Caron 2007. We also observed increases in both the abundance and grazing rates of microzooplankton within the 2 high pCO 2 treatments relative to ambient pCO 2 treatments.…”
supporting
confidence: 81%
“…The significant grazing pressure that we observed is consistent with the results of previous work within the JGOFS and BOFS studies of prymnesiophytedominated phytoplankton communities in the North Atlantic spring bloom (Burkill et al 1993, Verity et al 1993b, Fileman & Leakey 2005. These studies and others include reports of microzooplankton dominance of total phytoplankton herbivory and microzooplankton consuming significant portions of phytoplankton daily production in the North Atlantic (Gifford et al 1995, Stelfox-Widdicombe et al 2000.Increases in microzooplankton abundance and grazing mortality by Day 8 of the experiment in the 2 high temperature treatments were consistent with the known effects of increased temperature on protistan Mar Ecol Prog Ser 388: [27][28][29][30][31][32][33][34][35][36][37][38][39][40] 2009 physiological rate processes (Eppley 1972, Rose & Caron 2007. We also observed increases in both the abundance and grazing rates of microzooplankton within the 2 high pCO 2 treatments relative to ambient pCO 2 treatments.…”
supporting
confidence: 81%
“…In this context, several authors have reported positive net phytoplankton growth rates in long-term incubations using the dilution method in oligotrophic waters (e.g. Stelfox-Widdicombe et al 2000, Quevedo & Anadón 2001; however, these rates showed a large degree of spatial variability and, in some experiments, negative net growth rates were measured (see Fig. 2 in Quevedo & Anadón 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The grazing impact and feeding activity of planktonic ciliates have been investigated in many studies (Pierce & Turner 1992 and references therein) using different approaches, either offering labeled or unlabeled prey, or prey analogues to single ciliate species (Rassoulzadegan 1982, Jonsson 1986, Bernard & Rassoulzadegan 1990, Kivi & Setälä 1995 or using the dilution method (Landry & Hassett 1982) at the community level (Burkill et al 1987, Paranjape 1987, Gifford 1988, Stelfox-Widdicombe et al 2000. The cell content method has been employed in laboratory experiments to estimate ingestion and digestion of single species of ciliates (Dolan & Coats 1991, Dolan & 2imek 1997.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%